Biomass-powered thermal weeding in wine farms: An environmental and economic assessment. (20th January 2023) - Morselli, Nicolò; Boccaletti, Simone; Meglioraldi, Stefano; Puglia, Marco; Pedrazzi, Simone; Allesina, Giulio
Abstract: The energy transition in agriculture must be accompanied by agronomic practices that shift production towards organic regimes. Among the energy consuming processes that today find resistance in organic conversion there is certainly the removal of weeds from crops, that is mainly carried out through herbicides. This analysis evaluates the economic and environmental implications that the introduction of innovative thermal weeding systems, powered by biomass gasification, can have in the substitution of traditional chemical and mechanical weeding technologies. The comparison is carried out through a combination of cost–benefit analysis, environmental analysis and sensitivity analysis applied to the case study of vineyard management in northern Italy. The results show that the biomass-powered weeding system is economically feasible when it can benefit from economic incentives that reward organic production. In all cases, biomass-powered weeding system provides for a reduction in equivalent CO 2 emissions which reaches −75% in the case of replacement of glyphosate-based chemical weeding methods. The analysis points out that gasification-powered weeding process can also achieve carbon neutrality through the co-production of biochar, which should lead policy makers to support this practice under the environmental objectives at national and European level. Graphical abstract: Highlights: Woody biomass can substitute herbicides in vineyards weed control. The analyses show a 75% cut in greenhouse gases emissions. The shift is cost-effective if organic production is economically incentivized. Carbon neutrality can be achieved thanks to the production of biochar.